2015
DOI: 10.1515/ap-2015-0113
|View full text |Cite
|
Sign up to set email alerts
|

Dog’s genotype of Giardia duodenalis in human: first evidence in Europe

Abstract: The unicellular parasite Giardia duodenalis has been divided to eight assemblages (A-H) from which A and B have the most important zoonotic potential. All remaining genotypes have a strong commitment to various host animals. We present here the first clinical case of a human infection with the dog-specific genotype C of G. duodenalis in Slovakia. The patient, 44-year-old woman, suffered from long-term diarrhoea, abdominal pain, anorexia, weight loss, severe itching and dermatitis in the perianal area. The init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The remaining six assemblages (C to H) are host-specific (Feng and Xiao, 2011;Ryan and Caccio, 2013;Santin et al, 2012). However, assemblages C, D, E, and F have been reported from human at lower frequency in sporadic cases (Feng and Xiao, 2011;Liu et al, 2014;Strkolcova et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…The remaining six assemblages (C to H) are host-specific (Feng and Xiao, 2011;Ryan and Caccio, 2013;Santin et al, 2012). However, assemblages C, D, E, and F have been reported from human at lower frequency in sporadic cases (Feng and Xiao, 2011;Liu et al, 2014;Strkolcova et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…The remaining six assemblages (C to H) are host-specific (specific to animals). However, assemblages C, D, E, and F have been reported to cause human giardiasis in rare cases [ 3 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…cysts only in dogs less than 1 year, the percentage reached to 1.9%. Zoonotic potential of Giardia is limited, but con rmed transmission of speci c assemblage C from dog to human indicates a risk for immunode ciency patients [11]. Using molecular biological methods we have focused on dangerous zoonotic tapeworms.…”
Section: Discussionmentioning
confidence: 99%
“…German research study has shown that dogs predominantly host speci c Giardia assemblages C and D, but zoonotic assemblage A has also been proved in dogs [10]. Con rmed transmission of speci c assemblage C from dog to human pointed out to the immunode ciency in patients as an important risk factor [11].…”
Section: Introductionmentioning
confidence: 99%